2014
DOI: 10.3390/ijerph111112015
|View full text |Cite
|
Sign up to set email alerts
|

Smoke-Free Homes and Home Exposure to Secondhand Smoke in Shanghai, China

Abstract: Few studies have examined home exposure to secondhand smoke (SHS) in China. This study aimed to document: (1) the prevalence and correlates of exposure to SHS in homes (in adult non-smokers) in Shanghai, and (2) enforcement of rules, harm reduction behaviors, and self-efficacy for maintaining smoke-free homes in Shanghai. A total of 500 participants were recruited using a multistage proportional random sampling design in an urban and suburban district to complete a survey. Among the total 355 nonsmokers, 127 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
5
23
0
Order By: Relevance
“…The sense of helplessness amongst the women was striking and this parallels the findings of studies from South and Southeast Asia which have similarly observed women’s inability to negotiate smoke free homes [21,22,25]. These authors attribute this to gender inequity and gendered power interactions.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The sense of helplessness amongst the women was striking and this parallels the findings of studies from South and Southeast Asia which have similarly observed women’s inability to negotiate smoke free homes [21,22,25]. These authors attribute this to gender inequity and gendered power interactions.…”
Section: Discussionsupporting
confidence: 74%
“…SHS exposure is more among women from rural areas and those with low education. Studies done in Cambodia, China and India highlight women’s inability to negotiate smoke free homes [21,22]. This is true even when women are pregnant [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be a reflection of cultural differences such that certain Asian American populations are particularly sensitive to accommodating guests or others present in their homes. 5153 It is also interesting to note that being African American was associated with a greater likelihood of allowing hookah and marijuana use in the home in bivariate analyses, but these results did not hold in the regression models. In this sample, African Americans were more likely to be hookah and marijuana users, 45 so the regression results may have accounted for race via these variables.…”
Section: Discussionmentioning
confidence: 97%